Presentation of Pericardial Effusion in an 18-Year-Old Female with Systemic Lupus Erythematosus - Shafira Nurul Annisa; Rini Istisakinah (The Indonesian Journal of General Medicine, 2025)
Background: Pericardial effusion is a common manifestation of Systemic Lupus Erythematosus (SLE), a chronic autoimmune disease affecting young women. This rare symptom requires high suspicion and prompt diagnosis for appropriate treatment, emphasizing the importance of early detection and management. Case Description: A patient with pericardial effusion presented to the emergency department with symptoms such as weakness, mouth ulcers, and nausea. Despite no known medical conditions, a chest X-ray revealed cardiomegaly, suggesting an underlying cardiovascular condition. An echocardiographic evaluation revealed normal diastolic function and right ventricular contractility, but a moderate to severe pericardial effusion was identified. The patient was diagnosed with massive complex pericardial effusion, hypoalbuminemia, inflammatory anemia, and SLE. A multidisciplinary approach was implemented, including intravenous fluid therapy, corticosteroid therapy, gastroprotective therapy, anti-inflammatory therapy, and Video-assisted thoracoscopic surgery (VATS) pericardiotomy. Discussion: Pericardial effusion, a cardiac manifestation in SLE patients, is often caused by autoimmune-mediated inflammation of the pericardium. This inflammatory process, driven by autoantibodies and immune complexes, increases vascular permeability and facilitates fluid exudation, potentially leading to cardiac tamponade, requiring a multidisciplinary approach. Conclusion: Pericardial effusion in young SLE patients requires early recognition and multidisciplinary management, including VATS pericardiotomy. Treatment includes corticosteroids, immunosuppressive agents, and targeted antibiotics. Serial echocardiographic assessments and ongoing immunosuppressive therapy are crucial for long-term disease management.